"Purple Drank" (Codeine and Promethazine Cough Syrup): A Systematic Review of a Social Phenomenon with Medical Implications. Issue 5 (19th October 2020) - Miuli, A.; Stigliano, G.; Lalli, A.; Coladonato, M.; D'Angelo, L.; Esposito, F.; Cappello, C.; Pettorruso, M.; Martinotti, G.; Schifano, F; Di Giannantonio, M.
ABSTRACT: In the early 1990s, several studies reported the misuse of codeine and promethazine hydrochloride cough syrup. Since then, the combination of this pharmaceutical, together with sprite or alcohol, known on the streets as "purple drank" or "lean", has become a popular drug among rap singers who promote its tranquilizing and euphoric effects through their music and videos. This review examines the "purple drank" phenomenon, taking into consideration its clinical and social implications. The study was conducted using PubMed, Scopus, and Web of Science as search engines, applying several inclusion and exclusion criteria and the string "Purple AND drank", resulting in 138 records. Seven papers that met our criteria were found. The risk of bias assessment, when applicable, was also considered, resulting in a low level of risk. Epidemiological data highlighted a heterogeneous diffusion of the misuse of this mixture, which is not exclusively linked to a specific type of user (African-American teenagers, athletes, and rappers), as previously reported in American newspapers and in the social media. New digital tools should be taken into consideration for further social and medical evaluations of this phenomenon.